How Do We Learn Now? Pluralising Urban Pedagogies in the COVID-19 Pandemic. (May 2022) - Wesely, Julia; Lall, Ruchika; Dutta, Nandini; Anand, Geetika; Allen, Adriana
Since 2020, pedagogues and learners in the field of urban planning and practice have rapidly responded to new demands and realities posed by the COVID-19 pandemic. These have included shifting the modes and sites of learning from classrooms to screens, developing new programmes to build urgently required local capacities, fostering partnerships and platforms that sustain remote ways of learning together, and facilitating multi-sensorial and inclusive learning practices. This plurality of pedagogic adaptation and innovation suggests complex and nuanced relations with urban (in)equality, going beyond the dominant narrative of the digital divide and distributive inequalities in higher education. This article reflects on three experiences of critical pedagogies undertaken by researchers and activists, social movements and organised civil society from India, Brazil and Argentina. As the impacts of the pandemic on the nexus between urban practice and pedagogy unfold, we argue that these reflexions-in-action on decisions made, along with their underlying principles, are important stimuli for pluralising questions of what, where, with whom and how we learn to respond to urban inequalities. Moreover, they open nuanced discussions to strategically reimagine future hybrid learning trajectories to support pathways to urban equality.